Pengaruh Struktur Modal, Risiko Bisnis, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Sub Sektor Real Estate Dan Properti Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Pascalina Van Sweet Sesa; Rama Soyan Arung Lamba; Kurniawan Patma; Rudiawie Larasati (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This research aims to empirically examine the influence of capital structure, business risk, sales growth and company size on financial performance both partially and simultaneously in real estate and property sub-sectors located on the Indonesia Stock Exchange 2015-2020. This type of research is quantitative research. The data used is secondary data. A population of 77 companies with sampling techniques is the purposive sampling method. A sample of 10 companies was obtained multiplied by 6 years so that the sample obtained as much as 60 financial statement data. The analysis method used is multiple regression analysis with the help of SPSS21. Statistical results on variable capital structure (X1) value tcalculated smaller than ttable (-1,276 < 2.005) with significantly greater than 0.05, business risk variable (X2) value tcalculates greater than ttable (44,228 > 2.005) with a significant smaller than 0.05, sales growth variable (X3)calculated value t smaller than ttable (-0.288 < 2.005) with a significant larger than 0.05, company size variable (X4) number tcount value smaller than ttable (1,267 < 2.005) with a significant greater than 0.05. Simultaneously from the statistical results it is known that the value of Fcalculates greater than the value of Ftable (611,856 > 2.54), with a value of significance (0.000 < 0.05).. The results of this study showed that variables in capital structure, sales growth and company size partially had no effect on financial performance and business risk variables partially had a significant effect on financial performance. While the variables of capital structure, business risk, sales growth and company size simultaneously affect financial performance.